Orchestral performance practices in the nineteenth century: Size, proportions, and seating - Koury, Daniel J. (Rochester Boydell & Brewer, 1991)
" . . . supported by a wealth of information --- often novel and fascinating --- which the author has collected from a great variety of sources. Admirable industry, sound judgement, and excellent style have produced a book that ought to be in the hands of every conductor."--- Max Rudolf Journal of the Conductors' Guild". . . an essential book for anyone trying to give responsible performances of 19th-century music." --- Early Music News